Intellectual capital factors at work in Dominican firms: Understanding their influence - Víctor Gómez-Valenzuela (Journal of Innovation and Entrepreneurship, 2022)
From an empirical-based perspective, this paper explores the influence of intellectual capital factors on the performance of firms in the Dominican Republic. A Likert scale from one to seven was used to capture firms' sensitivity to human, structural and relational capital factors. An exploratory factor analysis was carried out using the method of principal components with VARIMAX rotation. The final factorial scores were standardized to execute the regression analysis. Structural capital factors appear to be the dominant intellectual capital components within the Dominican context. Human capital factors play a vital role in performance in manufacturing and in-services firms, and relational capital factors are significant in determining their performance. This research contributes to the regional literature on intellectual capital studies in Latin America and the Caribbean. It puts forward some specific points related to the role of intellectual capital factors in explaining firms' performance in small open economies such as that of the Dominican Republic.
Keywords: 650; Dominican Republic; Firms' performance; Intangibles; Intellectual capital